Barriers Face by Nurses Regarding Proper Nursing Documentation at Teaching Hospitals Peshawar Pakistan - Afrooz Bibi, Najma Naz, Sardar Ali, Barkatullah, Muhammad Naeem Awan, Amir Sultan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To explore the barriers faced by nursing staff in proper nursing documentation at the tertiary care hospital of Peshawar Pakistan. Methodology: A qualitative case-study design was used, having a 12 sample size as a result of data saturation, while the data was collected using purposive sampling technique in the two tertiary care hospital of Peshawar. The data was collected in the November 2022. A semi-structure interview was conducted with each participant using a topic guide where the interview lasts for 60 to 90 minutes. The data was translated from Urdu to English, while the thematic analysis based on Braun and Clarke six steps used for analysis. The study was approved by the advance studies and research board and ethical review board of Khyber medical university Peshawar. Results: Four themes were emerged that was individual issues, incompetence’s in documentation, technical issues and organizational issues. Conclusion: The study indicates that documentation is vital component of quality care that are affected by shortage of staff, lack of training, heavy workload, managerial issues like verbal commands, ambiguous writing, individual issues like lack of motivation, coordination, time and knowledge, and software and hardware issues create challenges for nurses in their documentation. Keywords: Nursing documentation, nursing practice, barriers, nursing staff